Bullous systemic lupus erythematosus - a case report - Eduardo Messias Hirano Padrão; Lucas Faria Teixeira; Celina Wakisaka Maruta; Valéria Aoki; Aloisio Souza Felipe da Silva; Elizabeth In Myung Kim; Luciana Avena Smelli (University of São Paulo, 2019)
Skin involvement in systemic lupus erythematosus (SLE) occurs in more than 75% of patients with this condition. Vesicles and blisters in lupus erythematosus (LE) may be present in SLE secondary to interface vacuolar changes in the epidermis, in discoid LE also secondary to vacuolar epidermal changes, and in bullous LE secondary to antibodies anti-collagen VII deposits with neutrophilic aggregates. In addition, blisters can occur due to the association of SLE with other autoimmune blistering diseases (e.g. bullous pemphigoid). BSLE is a rare blistering disease that mainly occurs in females (30-40 years old), and less frequently in children and adolescents. The most common presentation is rapid and widespread development of tense vesicles and bullae over erythematous macules or plaques. Preferential sites are: superior trunk, proximal superior limbs, and face (lips) with symmetrical distribution. Mucosal involvement is common on perioral, pharyngeal, laryngeal, and genital areas. The involvement of sun-exposed areas is not mandatory. The lesions usually progress with no scarring, but hypo or hyperchromia may be present. We report an 18-year-old female patient with blistering lesions at admission, who was diagnosed with BSLE. She was initially treated with systemic prednisone and hydroxychloroquine. Her condition evolved with relapsing lesions, which required the introduction of Dapsone. The authors emphasize the relevance of recognizing BSLE-a rare presentation of SLE-which may evolve with marked clinical presentation.